Determination of sterigmatocystin in foods in Japan: method validation and occurrence data. Issue 9 (2nd September 2019) - Yoshinari, Tomoya; Takeuchi, Hiroshi; Kosugi, Masaki; Taniguchi, Masaru; Waki, Masumi; Hashiguchi, Shigeki; Fujiyoshi, Tomoharu; Shichinohe, Yaeko; Nakajima, Masahiro; Ohnishi, Takahiro; Hara-Kudo, Yukiko; Sugita-Konishi, Yoshiko
ABSTRACT: A survey of the contamination of foods by sterigmatocystin (STC) was performed by an analytical method based on LC-MS/MS. STC was extracted from samples with acetonitrile/water (85/15, v/v) and then purified with immunoaffinity columns. The method was validated by a small-scale inter-laboratory study using spiked wheat samples. Mean recoveries of STC were 100.3% and 92.5% from two samples spiked at 0.5 and 5.0 µg/kg, respectively. A total of 583 samples were analysed between 2016 and 2018, and STC was detected in 19.9% of all samples at >0.05 μg/kg (limit of quantification). The foods that were contaminated by STC were wheat flour, Job's tears products, rye flour, rice, buckwheat flour, white sorghum, barley products, azuki bean and corn flour. STC was not found in beer or wine. The occurrence of STC in domestic wheat flour (44.4%), Job's tears products (41.7%) and rye flour (29.9%) accounted for the three highest values. The highest mean concentrations were obtained for Job's tears products (0.3 μg/kg) and rye flour (0.3 μg/kg). The maximum contamination level was present in a sample of rye flour (7.1 μg/kg). Although the contamination levels were low, these results indicate that STC frequently contaminates Japanese retail foods. A continuous survey is required to assess exposure to STC in Japan.